Chemical composition and antioxidant activities of essential oil of Hedychium greenii and Hedychium gracile from India. Issue 10 (19th May 2019) - Ray, Asit; Jena, Sudipta; Kar, Basudeba; Patnaik, Jeetendranath; Panda, Pratap Chandra; Nayak, Sanghamitra
Abstract: The chemical constituents of the essential oils hydrodistilled from rhizome parts of Hedychium greenii W.W. Sm. and Hedychium gracile Roxb, of family Zingiberaceae, growing in India, were analysed for the first time by GC-FID and GC-MS, respectively. A total of 30 and 29 components representing 99.62 and 96.74% of the total oil were identified in the essential oils of H. greenii and H. gracile, respectively. The major components of H. greenii were bornyl acetate (31.32%), α -pinene (14.49%), camphene (12.81%) and limonene (10.55%), whereas H. gracile was dominated by β -pinene (25.24%), γ -terpinene (24.62%), terpinen-4-ol (14.87%) and 1, 8-cineole (7.51%). Essential oils were assessed for antioxidant potential using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2′-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical scavenging assay. H. greenii oil exhibited stronger antioxidant potential as compared to H. gracile oil and butylated hydroxytoluene (BHT). Thus, H. greenii rhizome oil has the potential to be used as an alternative source of antioxidant. Abstract :